Using Combined Methods of Genetic Mapping and Nanopore-Based Sequencing Technology to Analyze the Insertion Positions of G10evo-EPSPS and Cry1Ab/Cry2Aj Transgenes in Maize - Peng, Cheng; Mei, Yingting; Ding, Lin; Wang, Xiaofu; Chen, Xiaoyun; Wang, Junmin; Xu, Junfeng (Frontiers in Plant Science, 2021)
The insertion position of the exogenous fragment sequence in a genetically modified organism (GMO) is important for the safety assessment and labeling of GMOs. SK12-5 is a newly developed transgenic maize line transformed with two trait genes [i.e., G10evo-5-enolpyrul-shikimate-3-phosphate synthase (EPSPS) and Cry1Ab/Cry2Aj] that was recently approved for commercial use in China. In this study, we tried to determine the insertion position of the exogenous fragment for SK12-5. The transgene–host left border and right border integration junctions were obtained from SK12-5 genomic DNA by using the thermal asymmetric interlaced polymerase chain reaction (TAIL-PCR) and next-generation Illumina sequencing technology. However, a Basic Local Alignment Search Tool (BLAST) analysis revealed that the flanking sequences in the maize genome are unspecific and that the insertion position is located in a repetitive sequence area in the maize genome. To locate the fine-scale insertion position in SK12-5, we combined the methods of genetic mapping and nanopore-based sequencing technology. From a classical bulked-segregant analysis (BSA), the insertion position in SK12-5 was mapped onto Bin9.03 of chromosome 9 between the simple sequence repeat (SSR) markers umc2337 and umc1743 (26,822,048–100,724,531 bp). The nanopore sequencing results uncovered 10 reads for which one end was mapped onto the vector and the other end was mapped onto the maize genome. These observations indicated that the exogenous T-DNA fragments were putatively integrated at the position from 82,329,568 to 82,379,296 bp of chromosome 9 in the transgenic maize SK12-5. This study is helpful for the safety assessment of the novel transgenic maize SK12-5 and shows that the combined method of genetic mapping and the nanopore-based sequencing technology will be a useful approach for identifying the insertion positions of transgenic sequences in other GM plants with relatively large and complex genomes.